Methodical instructions for the performance of control work in the discipline "Fundamentals of engineering training" - Yevtushenko, Nataliіa Serhiivna; Semenov, Yevhenii Oleksandrovych (National technical university "Kharkov politechnical institute", 2024)
The strategic position of each state in the world economy is determined by the level of development of machine-building, which is the basis of technical re-equipment of the entire economy. The system of training specialists in the field of machine-building in Ukraine is now gaining national importance. At the stage of formation of specialists in maintenance of machine-building productions it is necessary to help future young specialists to understand bases of technological essence of process of manufacturing of products on the basis of that rich heritage which for several generations was created by domestic scientists, designers, technologists and machine-building workers. At the same time, first of all, it is necessary to understand that the term "engineer" means a specialist with higher technical education. The role of engineering and technical workers in the field of labor protection of mechanical engineering is important. The future engineer must know well - what consists of his activities in the enterprise, engineering heritage, the ratio of scientific and technical activities and other issues. The course "Fundamentals of Engineering Training" will help him in this.
Keywords: fundamentals of engineering training; machine-building productions; machines; technical quality control